The Muse that Sings: Composers Speak about the Creative Process - McCuthan, Ann (Oxford Oxford University Press, 1999)
The Muse That Sings is a unique behind-the-scenes look at both twentieth-century music and the nuts and bolts of creative work. Here, twenty-five of America's leading composers--from Adams to Zorn, from Bolcom to Vierk--talk candidly about their craft, their motivations, their difficulties, and how they how proceed from musical idea to finished composition.While focusing on the process and the stories behind specific works, the composers also touch on topics that will interest anyone involved in creative work. They discuss teachers and mentors, the task of revision, relationships with performers, and the ongoing struggle for a balance between freedom and discipline.They reveal sources of inspiration, artistic goals, and the often unexpected ways their musical ideas develop. Some describe personal tonal systems; others discuss the impact of computers and other electronic tools on their work; still others reflect philosophically on the inner impulses and outer influences that continue to drive them.
Keywords: Adams, John -- 1947-; Zorn, John; 20th Century (1901-2000); Composer; Composing; Interview; Creativity; USA